2017
DOI: 10.1155/2017/8248725
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Metabolism in Nonobese Patients with Type 2 Diabetes Following the Acute Restoration of Normoglycaemia

Abstract: This study investigated how acute restoration of normoglycaemia affected energy metabolism during exercise in nonobese patients with type 2 diabetes. Six subjects (mean ± SEM) aged 56.2 ± 2.7 years, with a BMI of 24.5 ± 1.5 kg/m2 and a VO2 peak of 28.7 ml/kg/min, attended the lab on two randomised occasions for a four-hour resting infusion of insulin or saline, followed by 30 minutes cycling at 50% VO2 peak. During the 4 h resting infusion, there was a greater (P < 0.0001) reduction in blood glucose in insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…Seiring dengan hal tersebut, penurunan massa otot pun dapat dihambat dengan meningkatkan sintesis protein di otot melalui efek aktivitas fisik (Colberg et al, 2016). Selain itu, aktivitas fisik pada pasien DM tipe 2 dapat memperbaiki IMT, memperbaiki sensitivitas insulin, dan mencegah komplikasi (Gaffney, Mansell, Stephens, Macdonald, and Tsintzas, 2017;Gray, Picone, Sloan, and Yashkin, 2016;Sudarsono, 2015). Berlawanan dengan hal tersebut, tren aktivitas fisik saat ini menunjukkan pergeseran ke arah negatif akibat kemajuan teknologi di zaman modern (WHO, 2011).…”
Section: Systematic Literatur Riviewunclassified
“…Seiring dengan hal tersebut, penurunan massa otot pun dapat dihambat dengan meningkatkan sintesis protein di otot melalui efek aktivitas fisik (Colberg et al, 2016). Selain itu, aktivitas fisik pada pasien DM tipe 2 dapat memperbaiki IMT, memperbaiki sensitivitas insulin, dan mencegah komplikasi (Gaffney, Mansell, Stephens, Macdonald, and Tsintzas, 2017;Gray, Picone, Sloan, and Yashkin, 2016;Sudarsono, 2015). Berlawanan dengan hal tersebut, tren aktivitas fisik saat ini menunjukkan pergeseran ke arah negatif akibat kemajuan teknologi di zaman modern (WHO, 2011).…”
Section: Systematic Literatur Riviewunclassified
“…The hormonal response to exercise could be affected in diabetes: postprandial suppression of glucagon, increase of GLP-1, and no change in insulin levels was observed in diabetes patients one day after performing two long bouts of exercise (13). Although other studies have shown no change in insulin levels after acute sessions of aerobic exercise (14,15), other authors reported a reduction in these levels (16), while glucagon levels were found to have increased after aerobic exercise (17), and GLP-1 levels decreased during post-dinner resistance exercise (18). Thus, the present study aimed to evaluate glucose variability and hormonal responses during and after an aerobic exercise session performed after breakfast in type 2 diabetes subjects, treated with metformin.…”
Section: Introductionmentioning
confidence: 99%